Effects of parenteral fish-oil emulsion (Omegaven) on cutaneous wound healing in rats treated with dexamethasone - BOZKURT, SÜHEYLA (SAGE PUBLICATIONS INC, 2007)
Background: The aim was to assess wound healing when parenteral fish-oil emulsion is given to rats receiving dexamethasone. Methods: For 5 days after skin wounding, group S (control; n = 7) received saline 1 mL/kg intraperitoneal (IP); group D (n = 7), dexamethasone 0.2 mg/kg IP; and group DO (n = 9), dexamethasone 0.2 mg/kg IP plus 1 mL/kg Omegaven (Fresenius Kabi, Austria). Wound specimens were assessed for hydroxyproline level, wound depth, histology (epidermal/dermal regeneration, granulation tissue thickness, and angiogenesis), and. expression of transforming growth factor-P (TGF-P) and platelet-derived growth factor-AA (PDGF-AA). Results: Compared with D and DO specimens, controls had higher hydroxyproline (p <.01), deeper wounds (p <.05), and better histologic scores (p <.01 angiogenesis; others p <.05). There were no significant differences between the group D and DO means for hydroxyproline level, wound depth, or histologic scores (p >.05 for all). Controls had higher TGF-P expression scores than the other groups (p <.01 for both) and a higher PDGF-AA expression score, than group DO (p <.01). Groups D and DO had statistically similar TGF-p scores, but group D had a higher PDGF-AA score (2.71 +/- 0.75 vs 1.55 +/- 0.72, respectively; p <.05). Conclusions: According to the parameters we studied, adding parenteral. omega-3 and omega-6 fatty acids to the nutrition regimen of rats treated with dexamethasone does not seem to have adverse effects on wound healing, and effects on wound healing may not need to be considered when determining if these agents should be supplemented in nutrition support regimens.
Keywords: GROWTH-FACTOR-BETA; MESSENGER-RNA; FATTY-ACIDS; TISSUE; OMEGA-3-FATTY-ACIDS; INHIBITION; ESOPHAGEAL; SINGLE; IMPACT; REPAIR